Characterization of a Baculovirus-Encoded RNA 5′-Triphosphatase - Gross, Christian H. (American Society for Microbiology, 1998)
Autographa californica nuclear polyhedrosis virus (AcNPV) encodes a 168-amino-acid polypeptide that contains the signature motif of the superfamily of protein phosphatases that act via a covalent cysteinyl phosphate intermediate. The sequence of the AcNPV phosphatase is similar to that of the RNA triphosphatase domain of the metazoan cellular mRNA capping enzyme. Here, we show that the purified recombinant AcNPV protein is an RNA 5′-triphosphatase that hydrolyzes the γ-phosphate of triphosphate-terminated poly(A); it also hydrolyzes ATP to ADP and GTP to GDP. The phosphatase sediments as two discrete components in a glycerol gradient: a 9.5S oligomer and 2.5S putative monomer. The 2.5S form of the enzyme releases (32)P(i) from 1 μM γ-(32)P-labeled triphosphate-terminated poly(A) with a turnover number of 52 min(−1) and converts ATP to ADP with V(max) of 8 min(−1) and K(m) of 25 μM ATP. The 9.5S oligomeric form of the enzyme displays an initial pre-steady-state burst of ADP and P(i) formation, which is proportional to and stoichiometric with the enzyme, followed by a slower steady-state rate of product formation (approximately 1/10 of the steady-state rate of the 2.5S enzyme). We surmise that the oligomeric enzyme is subject to a rate-limiting step other than reaction chemistry and that this step is either distinct from or slower than the rate-limiting step for the 2.5S enzyme. Replacing the presumptive active site nucleophile Cys-119 by alanine abrogates RNA triphosphatase and ATPase activity. Our findings raise the possibility that baculoviruses encode enzymes that cap the 5′ ends of viral transcripts synthesized at late times postinfection by a virus-encoded RNA polymerase.